User Satisfaction Analysis of the Ogan Ilir Disdukcapil Population Administration Online Service Information System Using the HOT FIT Model Method - Fauzan, Ahmad Aulia (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
This study describes how to analyze user satisfaction of the Population Administration Service Information System of Dukcapil Ogan Ilir. This study aims to determine the satisfaction of users of the Population Administration Service Information System (SIAK) Dukcapil Ogan Ilir by using the HOT FIT Model method. The research uses all perspectives that exist in the HOT FIT Model, namely Human, Organization and Technology. The data in this study were collected using a quantitative approach by distributing questionnaires to each respondent in the perspective of the people of Tanjung Batu sub-district in Ogan Ilir district. The results of this study are expected to produce user satisfaction on the system as input for improving the Population Administration Information System (SIAK) dukcapil Ogan Ilir information system service in the future.